Evaluasi Kinerja Layanan dan Tingkat Kepuasan Pelanggan Angkutan Penyeberangan Amolengo-Pure Provinsi Sulawesi Tenggara - Rasyid, La Ode Ahmad; Lakawa, Irwan; Rahmat, La Ode Musa (Universitas Sulawesi Tenggara, 2021)
Indonesia is a large country that is widespread with it’s islands and is a country traversed by the Equator, so sea transportation has an important role to play in connecting one area to another, considering that Indonesia has a very wide ocean. One of the means of sea transportation that is widely used by the community is the ferry. Ferry is a type of sea transportation that can be used as passenger and goods transportation using certain routes or routes. With the existence of the Ferry port, it can increase the acceleration of development in the area, especially Amolengo Village, Konawe Selatan Regency. The Amolengo ferry port is a port that serves the crossing of passengers and goods that connects the South Konawe mainland and its surroundings with Buton Island, where the destination port is Pure port. The quality of good service provided is one of the determining factors for the success of the company. The research method is arranged by interviewing respondents by answering the questions on the questionnaire. The analysis was performed using Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results of this study indicate that the consumer satisfaction index on the performance of the Amolengo - Pure Ferry Port, Southeast Sulawesi Province is 84.6% and is in the range 0.81 - 1.00 indicating that consumers are very satisfied with the service quality of the Amolengo - Pure Ferry Port, Southeast Sulawesi Province.